Data Mining Rough Set Method In Analyzing Communities Disposing of Garbage in Rivers - Sanny Edinov; Rezki Fauzi (TIERS Information Technology Journal, 2023)
The waste management approach is a worldwide problem and is often neglected. The situation in urban areas is worse than in rural areas. It is a big challenge to deal with this dilemma, therefore, the management of a better management system is inevitable. The input data used in this study included the community's last educational data and social stratification, both through questionnaires and interviews with the community. Furthermore, the data that has been presented in the decision system is collected or eliminated for each object that has the same attributes, then summed and collected into the same class so that the cleaning technique process becomes simple (equivalent class). The Advanced Discernibility Matrix and the Discernibility Modulo D Matrix will compare a collection of attributes based on the equivalence class that will be modeled with the last Education modeled "A", the social stratification of society is modeled "B". The reduction results obtained reveal that there are several reasons why people throw garbage in the river. This provides information, the latest differences in social stratification and education can influence people's mindset and habits of disposing of garbage. The social stratification of people who are not from the wealthy class and have the last elementary-junior high school education contributes more negatively to the fullness of the river flow with garbage.